Regulatory Multitasking of Tolerogenic Dendritic Cells – Lessons Taken from Vitamin D3-Treated Tolerogenic Dendritic Cells - Nikolic, Tatjana; Roep, Bart (Frontiers in Immunology, 2013)
Tolerogenic dendritic cells (DCs) work through silencing of differentiated antigen-specific T cells, activation and expansion of naturally occurring T regulatory cells (Tregs), transfer of regulatory properties to T cells, and the differentiation of naïve T cells into Tregs. Due to an operational definition based on T cell activation assays, the identity of tolerogenic DCs has been a matter of debate and it need not represent a specialized DC subset. Human tolerogenic DCs generated in vitro using inhibitory cytokines, growth factors, natural immunomodulators, or genetic manipulation have been effective and several of these tolerogenic DCs are currently being tested for clinical use. Ex vivo generated tolerogenic DCs reduce activation of naïve T cells using various means, promote a variety of regulatory T cells and most importantly, frequently show stable inhibitory phenotypes upon repetitive maturation with inflammatory factors. Yet, tolerogenic DCs differ with respect to the phenotype or the number of regulatory mechanisms they employ to modulate the immune system. In our experience, tolerogenic DCs generated using the biologically active form of vitamin D (VD3-DCs), alone, or combined with dexamethasone are proficient in their immunoregulatory functions. These tolerogenic DCs show a stable maturation-resistant semi-mature phenotype with low expression of activating co-stimulatory molecules, no production of the IL-12 family of cytokines and high expression of inhibitory molecules and IL-10. VD3-DCs induce increased apoptosis of effector T cells and induce antigen-specific regulatory T cells, which work through linked suppression ensuring infectious tolerance. Lessons learned on VD3-DCs help understanding the contribution of different pattern-recognition receptors (PRRs) and secondary signals to the tolerogenic function and how a cross-talk between DCs and T cells translates into immune regulation.